FACTORS INFLUENCING THE INTENSITY OF CONSTRAINTS IN DAIRY FARMING DUE TO LUMPY SKIN DISEASE - E. Sangeetha; A. Serma Saravana Pandian; V. Senthilkumar; S. Sivaraman (Indian Journal of Veterinary and Animal Sciences Research, 2026)
The study was undertaken to identify and prioritize the constraints faced by dairy farmers due to lumpy skin disease. Primary data were collected from 80 dairy farmers across four districts of the Cauvery delta zone of Tamil Nadu, namely Tiruchirappalli, Thanjavur, Tiruvarur and Nagapattinam, using a structured and pre- tested interview schedule through the personal interview method. A Likert scale was employed to assess the intensity of constraints, and scores were computed to prioritize them. A multiple linear regression model was used to determine the socio-economic and farm-related factors associated with the intensity of constraints perceived by the dairy farmers due to lumpy skin disease. The study’s findings revealed that the foremost constraint perceived by the dairy farmers was the lack of vaccination programme, followed by the low price offered for diseased animals and the distant veterinary hospitals. The results of the regression analysis indicated that among the ten variables included, education, farm size, and age were found to have a negative and significant influence on the intensity of constraints, whereas the proportion of animals affected had a positive and significant influence. These findings underscore the importance of strengthening veterinary infrastructure, improving disease surveillance and enhancing farmer awareness to effectively mitigate the impact of lumpy skin disease and promote sustainable dairy farming.